Clinical codes combined with procedure codes increase diagnostic accuracy of Crohn's disease in a US Military health record. Issue 1 (26th February 2020) - Singla, Manish; Hutfless, Susan; Al Kazzi, Elie; Rodriguez, Benjamin; Betteridge, John; Brant, Steven
Abstract : Background and aims: Previous examinations of International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) codes to predict accuracy of diagnosis in inflammatory bowel disease have had limited chart review to confirm diagnosis. We aimed to evaluate using the ICD-9-CM for identifying Crohn's disease (CD) in a large electronic health record (EHR) database. Methods: This is a retrospective case-control study with a 3:1 allocation of EHRs of active duty service members diagnosed with CD from 1996 to 2012. Subjects were selected by having two ICD-9-CM codes for CD during the study period. Gastroenterologists reviewed each chart and confirmed the diagnosis of CD by analysing medication history and clinical, endoscopic, histological, and radiographic exams. Results: 300 cases of CD were selected; 14 cases were discarded due to lack of data, limiting our analysis to 284 subjects. Two diagnostic codes for CD had sensitivity, specificity, and positive predictive value (PPV) of 1.0, 0.53, and 0.69, respectively, for confirmed CD. If two encounters listing CD were with a gastroenterologist, the sensitivity, specificity, and PPV was 0.76, 0.81, and 0.80, respectively. If a colonoscopy was performed within 90 days of any three encounters with a CD code, the sensitivity, specificity, and PPV was 0.51, 0.94, and 0.89, respectively. Conclusions: The poor PPV of ICD-9-CM codes in making the diagnosis of CD should be taken into consideration when interpreting results and when conducting research using such codes. Limiting these codes to those patients who have been given this diagnosis by a gastroenterologist, or to those who have had a colonoscopy near the time of diagnosis, increases the PPV.